(untitled) (Baghdad Science Journal, 2014)
The present study aimed to use the magnetic field and nanotechnology in the field of water purification, which slots offering high efficiency to the possibility of removing biological contaminants such as viruses and bacteria rather than the use of chemical and physical transactions such as chlorine and bromine, and ultraviolet light and boiling and sedimentation and distillation, ozone and others that have a direct negative impact on human safety and the environment. Where they were investigating the presence in water samples under study Coli phages using Single agar layer method and then treated samples positive for phages to three types of magnetic field fixed as follows (North Pole - South Pole - Bipolar) and compare the results with samples of water treatment in the same conditions of the magnetic field with the addition of powder iron filings stated the results to the act synergistic to use a magnetic field with iron filling efficiency up to 100% better than the use of a magnetic field alone, where the disappearance of the emergence of spots Plaques treatment in the second. thus enhancing the possibility of making iron pipe nanoparticles to pump water in the treatment of water due to the high surface area (surface / volume). It is suggested that this could be used in the future in a wide range of water purification may be the best option for waste water treatment.